2021
DOI: 10.1002/fsn3.2119
|View full text |Cite
|
Sign up to set email alerts
|

Boysenberry and apple juice concentrate reduced acute lung inflammation and increased M2 macrophage‐associated cytokines in an acute mouse model of allergic airways disease

Abstract: Bioactive compounds including anthocyanins and other polyphenols are associated with reduced lung inflammation and improved lung function in asthma and other lung diseases. This study investigated the effects of a Boysenberry and apple juice concentrate, high in cyanidin glycosides, ellagitannins, and chlorogenic acid, on a mouse model of allergic airways inflammation. Male C57BL/6J mice were orally gavaged with 2.5 mg/kg of total anthocyanins (TAC) from BerriQi® Boysenberry and apple juice concentrate (0.2 mg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 75 publications
(92 reference statements)
0
6
0
Order By: Relevance
“…[ 38 , 39 ] reported that tannins and polyphenolics exhibit more DPPH scavenger action toward radicals. Phenolic as well as flavonoid compounds undertake as reducing agents, free radical hunters, and quenchers of single molecules of oxygen creation [ 40 ]. Furthermore, phenolic acids and flavonoids components play chief roles in the control of acute and chronic diseases including respiratory infirmities like asthma, emphysema and ARD [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 38 , 39 ] reported that tannins and polyphenolics exhibit more DPPH scavenger action toward radicals. Phenolic as well as flavonoid compounds undertake as reducing agents, free radical hunters, and quenchers of single molecules of oxygen creation [ 40 ]. Furthermore, phenolic acids and flavonoids components play chief roles in the control of acute and chronic diseases including respiratory infirmities like asthma, emphysema and ARD [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanically, PB2 inhibits foam cell formation and pyrin domain containing 3 inflammasome activation, and it activates PPARγ to induce M2 phenotype of mouse macrophages. All these beneficial effects may be attributed to the reduction of PB2 on the risk of atherosclerosis [16,[40][41][42][43]. However, the anti-atherosclerotic effects of PB2 on apoE −/− mice and the underlying mechanisms remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to those mentioned above, other polyphenolic compounds that demonstrated a broad spectrum of anti-inflammatory and anti-allergic effects in vitro have recently been intensively investigated in animal and clinical studies. For example, dietary supplementation of BerriQi ® Boysenberry and apple juice concentrate, containing high amounts of anthocyanins, ellagitannins, and chlorogenic acids, in OVA-challenged asthmatic mice can suppress immune cell infiltration in the lung, tissue damage, and mucus production as a result of regulation of innate immune pathways [295]. Similarly, the chestnut inner shell extract, as a rich source of gallic acid (a phenolic acid) and ellagic acid (a tannin), was found to present the anti-asthmatic efficacy inhibiting the inflammatory response induced by OVA challenge and relieving asthma symptoms, such as airway hyperresponsiveness and mucus overproduction in the asthma mice model [296].…”
Section: Asthmamentioning
confidence: 99%